Choice experiment attributes selection: problems and approaches in a modal shift study in Klang Valley, Malaysia - Kaffashi, Sara; Shamsudin, Mad Nasir; Ahmad Sidique, Shaufique Fahmi; Bazrbachi, Abdullatif; Radam, Alias; Abdul Rahim, Khalid; Usman, Adam Shehu (Canadian Center of Science and Education, 2016)
Choice experiment (CE) is a questionnaire based method that the accuracy of research questionnaire determines the validity of the research outcomes. Attribute selection has a prime importance in every CE studies. If respondents do not understand or do not have preference for a certain attribute, the attribute non-attendance problem might happen that biases overall results of the research. Qualitative approaches such as literature review, focus group discussion, and in depth discussion commonly applied in CE researches. However, especially in the developing countries context where ethnical and cultural diversity is a challenge in conducting survey based questionnaires, qualitative methods are not sufficient in selecting attributes. Present study investigates the application of relative importance index (RII) in respondents’ preference for attributes in a modal shift study in Klang Valley, Malaysia. The 5 point Likert scale questions were employed to enhance respondents’ preferences for initial 24 selected attributes. The results of this study showed that from 24 pre-selected attributes, only 18 of them had RII>0.5 and could be included in the final CE design. The results of this study could help researchers to control for unobserved problems in selecting the attributes which could not be discovered through qualitative approaches.